PELATIHAN PEMBUATAN SABUN CUCI CAIR PADA WARGA KAMPUNG BULAK PONDOK MELATI KOTA BEKASI - Mayarni; Kartikawati, Eka; Murwitaningsih, Susanti (DEVOSI, 2024)
The partner's problem is the lack of creativity to start an entrepreneurship. Partners include residents who are dominated by the lower middle economy. The survey results show that the residents work as teachers, office workers, factory workers selling snacks but this is only about five percent of the total local population. Other professions such as washing and scrubbing, traveling vegetable sellers, and construction workers are fewer than those who are unemployed. Furthermore, there are families who have the skills to make snacks such as chips, pecal and fried foods, but there are only about three to five families.  This means that the local community, especially housewives, is dominated by unemployed mothers who are supported by their husbands' income, which is dominated by irregular income. This problem has an impact on the disruption of children's schooling, domestic quarrels and even divorce. The solution that will be offered is to increase family income by entrepreneurship through making liquid laundry soap. Making this liquid laundry soap is not too difficult and the raw materials are also easy to obtain. The service method uses training and demonstration. The results of community service activities in making liquid laundry soap are very necessary, this is because it can be used as an alternative side entrepreneurship that is very profitable for the community.